Chronologie mochica : une nouvelle synthèse - Nino Del Solar; Rémy Chapoulie; Luis Jaime Castillo (Journal de la Société des Américanistes)
One of the issues in archaeological sciences is the establishment of chronological sequences in areas of human occupation. The main objective in this context is the reconstruction of the cultural diachronic processes connected to the emergence, the evolution, and the vanishing of the material cultures connected to human societies in specific environments. Concerning the Mochica (2th-10th century, north coast of Peru), recent archaeological research is pursued in order to explain such processes. In this article, we propose a revision and a synthesis of the given information on the relative chronology of this culture. Moreover, we present an inventory of Mochica 14C dates obtained during the last forty years. Thus the goal here is to reassess the temporal and stylistical data accepted by the archaeological community.